Real-time control of a hybrid laboratory plant using a receding horizon control strategy - Gambier, Adrián (Proceedings of the 2004 IEEE International Conference on Control Applications, 2005)
Real-time results of a receding horizon state-space controller, applied to a laboratory plant with hybrid characteristics, are reported in This work. The control strategy is based on a multi-model scheme and the corresponding switching logic. The control law involves a state-space receding horizon tracking system, a constant-disturbances compensator and a state and constant-disturbances estimator based on an augmented Kalman filter. The pilot plant consisting of three tanks, a pump and several valves exhibits nonlinear and hybrid behavior. Results are satisfactory and better than the results obtained for a unique controller.
Elektronische Reproduktion der Druckausgabe
Gesehen am 19.12.2019